2018
DOI: 10.1177/2164956118769006
|View full text |Cite
|
Sign up to set email alerts
|

Neural Mechanisms of Qigong Sensory Training Massage for Children With Autism Spectrum Disorder: A Feasibility Study

Abstract: ObjectivesDespite the enormous prevalence of autism spectrum disorder (ASD), its global impact has yet to be realized. Millions of families worldwide need effective treatments to help them get through everyday challenges like eating, sleeping, digestion, and social interaction. Qigong Sensory Training (QST) is a nonverbal, parent-delivered intervention recently shown to be effective at reducing these everyday challenges in children with ASD. This study tested the feasibility of a protocol for investigating QST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…A recent review on effectiveness and safety of manual lymphatic drainage in breast cancer patients led to the conclusion that such a treatment is safe and provides further advantages over other therapies aimed at decreasing swelling [10]. Consistent with our assumption, there are reports suggesting that massage improves the symptoms of autism [11] even though, in the paper by Jerger et al the massage was not performed with the specific goal of improving the flow of lymph through the deep cervical nodes.…”
Section: Introductionsupporting
confidence: 77%
“…A recent review on effectiveness and safety of manual lymphatic drainage in breast cancer patients led to the conclusion that such a treatment is safe and provides further advantages over other therapies aimed at decreasing swelling [10]. Consistent with our assumption, there are reports suggesting that massage improves the symptoms of autism [11] even though, in the paper by Jerger et al the massage was not performed with the specific goal of improving the flow of lymph through the deep cervical nodes.…”
Section: Introductionsupporting
confidence: 77%
“…Overall, several mechanisms may be involved in the development of Qigong's healthrelated benefits and the specific improvements in some cognitive functions [40][41][42][43]. These benefits may vary according to technique and population, and for that, systematic investigation in the field should be developed using standardised methods and well-developed studies.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al [ 45 ] indicated that improvement of oxytocin levels and the neural circuits involved in social interaction could be therapeutic for ASD. In a pilot study (not RCT design) by Jerger et al [ 46 ], heart rate variability (HRV) and cerebral oximetry of the prefrontal cortex were used to explore the neural mechanisms of Qigong massage intervention in 20 children with ASD.…”
Section: Discussionmentioning
confidence: 99%